Sistem Kendali pH dan Kekeruhan Air pada Aquascape menggunakan Wemos D1 Mini Esp8266 berbasis IoT - Abdul Rahman; Axel Natanael Salim (LPPM STT Terpadu Nurul Fikri, 2022)
Aquascape is the craft of arranging aquatic plants, rocks, caves, or driftwood aesthetically in an aquarium that essentially creates an underwater garden. For the living things in the aquascape to maintain their health and the water conditions to remain transparent, it is necessary to have continuous treatment to keep the water. For this reason, this study designed a device that can automatically control pH and water turbidity levels and can be monitored and controlled remotely. In the system developed in this study, sensors were used to monitor water conditions: temperature sensor, water pH sensor, HC-SR04 proximity sensor, and turbidity sensor. In contrast, the control system used Wemos D1 Mini ESP8266. In this system, the results of reading water temperature conditions, water saturation levels, and aquascape water levels will be processed by the controller for automatic control so that the requirements of the aquascape remain good. These data will also be sent to MQTT Explore for real-time monitoring through web browsing or smartphone. The results of testing the control system using the Wemos D1 Mini ESP8266 show that the aquascape water temperature can be maintained at a temperature of 220 – 250C, the pH of the water is in the range of 6.9-8, and the turbidity level of the water is at a value of 10-25 NTU.